2021
DOI: 10.1155/2021/9923434
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 Coexpression Gene Analysis and the Regulatory Network in Endometrial Cancer Based on Bioinformatics Analysis

Abstract: Gynecological malignancies are tumors of the female reproductive system, mainly cervical cancer, endometrial cancer, and ovarian cancer. Endometrial cancer (EC) is the most common gynecological malignant tumor in developed countries. The aim of this study was to construct a network of programmed cell death protein 1 (PD-1) coexpressed genes through bioinformatics analysis and screen the potential biomarkers of PD-1 in endometrial cancer. In addition, genes and pathways involved in PD-1 and modulating tumor imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The factor interacts with the protein β-catenin which is responsible for cell motility and malignant signal transduction (26). Furthermore, bioinformatic analyses demonstrated that PD-1/PD-L1 signaling pathways crucially control chemokines and signaling and effector proteins of immune cells (27). According to the widely accepted molecular EC subtyping by The Cancer Genome Atlas (TCGA) group, four distinct molecular EC subtypes can be defined, implying different prognoses for patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…The factor interacts with the protein β-catenin which is responsible for cell motility and malignant signal transduction (26). Furthermore, bioinformatic analyses demonstrated that PD-1/PD-L1 signaling pathways crucially control chemokines and signaling and effector proteins of immune cells (27). According to the widely accepted molecular EC subtyping by The Cancer Genome Atlas (TCGA) group, four distinct molecular EC subtypes can be defined, implying different prognoses for patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] In addition, since the first Programmed Death 1/PD-L1 inhibitor was approved, many immune checkpoint inhibitors have also been used in clinic. [8] In the field of immunotherapy, Cytotoxic T-lymphocyte antigen 4 and Programmed Death 1 immune checkpoints have marked a paradigm shift. [9] Inhibitors of immune checkpoints target these molecules by alleviating certain inhibitory pathways, thereby promoting the immune system ability to combat tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of immune-cell infiltration in tumors is very important, because the type of immune-cell infiltration in tumors mainly determines whether the balance tends to an anti-tumor or tumor-promotion immune response (7). Since the first PD-1/PD-L1 inhibitors were approved by the Food and Drug Administration (FDA) in 2014, many immune-checkpoint inhibitors have been used in clinical practice (8). Therefore, exploring the key immuneregulation genes and signaling pathways related to EC may clarify the critical molecular mechanisms of EC and improve the level of diagnosis and immunotherapy.…”
mentioning
confidence: 99%